Intergeneric and interspecific relationships in tribe Ricineae revealed by phylogenomics of the plastome and transcriptome - Liu, Wen-Xiang; Li, Guo-Bo; Zhou, Zhuo; Chen, Jia-Fu; Yu, An-Min; Liu, Ai-Zhong; Tian, Bin; Ye, Jun-Wei (Frontiers in Plant Science, 2025)
IntroductionThe taxonomy of Euphorbiaceae is extremely difficult, especially the phylogeny of closely related genera. In Ricinus, which embraces an important non-food oil-seed crop worldwide, Discocleidion and Speranskia are closely related genera based on molecular evidence (tribe Ricineae), however the intergeneric and interspecific relationship of the tribe is not well-resolved. MethodsPlastome and transcriptome were sequenced and assembled before maximum likelihood and Bayesian inference phylogenetic trees were reconstructed. Plastome features and comparative analyses were conducted. Morphological traits of the tribe were explored as supplement to the molecular data. ResultsThe newly sequenced plastomes ranged from 167,327 to 190,093 bp with typical circular quadripartite structures. The longest genome of S. tuberculata may due to higher number of simple sequence repeats. Natural selection pressure on chloroplast genes was relatively small and the tribe likely experienced a population contraction. The transcriptome assembly contig N50 of the tribe ranged from 1506 (D. rufescens) to 2489 bp (S. tuberculata). A total of 50,513 genes (S. cantonensis) to 78,048 genes (D. ulmifolium) were detected, and the GC content varied between 38.17% (S. cantonensis) and 40.01% (R. communis). The three genera formed a well-supported monophyletic lineage, confirmed by different genomic data using different methods. Discocleidion and Ricinus were supported to be closely related. In Speranskia, S. yunnanensis diverged first and the divergence of S. tuberculata and S. cantonensis was followed. Further, morphological similarities supported the monophyletic lineage and intergeneric and interspecific relationship. DiscussionThe relationship in the tribe Ricineae is clearly revealed by genomic and morphological data, providing a genetic basis for future comparative genomic investigations and phylogeny reconstruction of Euphorbiaceae.